2016
DOI: 10.3389/fpsyg.2016.01165
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Intentional Effort Enhances the Sense of Agency

Abstract: Sense of agency (SoA) refers to the feeling of controlling one’s own actions, and the experience of controlling external events with one’s actions. The present study examined the effect of strength of intentional effort on SoA. We manipulated the strength of intentional effort using three types of buttons that differed in the amount of force required to depress them. We used a self-attribution task as an explicit measure of SoA. The results indicate that strength of intentional effort enhanced self-attribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
28
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 27 publications
12
28
2
2
Order By: Relevance
“…Since participants in those studies rated positive and negative stimuli as equally arousing, arousal cannot readily explain such valence-dependent effects. Finally, two studies that specifically aimed to investigate effects of unspecific arousal on sense of agency both showed stronger sense of agency under high arousal conditions (Minohara et al 2016 ; Wen et al 2015 )—opposite to the effects of fear and anger states that we found here (high arousal states of negative valence).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Since participants in those studies rated positive and negative stimuli as equally arousing, arousal cannot readily explain such valence-dependent effects. Finally, two studies that specifically aimed to investigate effects of unspecific arousal on sense of agency both showed stronger sense of agency under high arousal conditions (Minohara et al 2016 ; Wen et al 2015 )—opposite to the effects of fear and anger states that we found here (high arousal states of negative valence).…”
Section: Discussioncontrasting
confidence: 77%
“…[for a thorough review of sense of agency research, please see (David et al 2008 ; Haggard 2017 )]. Two recent studies have demonstrated that unspecific arousal states (induced by colours or physical effort) increase people’s sense of agency over their actions (Minohara et al 2016 ; Wen et al 2015 ), while factors that decrease sense of agency will tend to reduce feelings of control and responsibility (Yoshie and Haggard 2013 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For "Slow, " participants were required (unintentional) to move their own hands faster to compensate for the visual lags they observed for the virtual hand. While greater intentional effort can produce greater agency (Minohara et al, 2016), greater unintentional effort may reduce perceived efficacy of user control, especially if it promotes feelings of inability to initiate faster speeds (Kawabe, 2013). In this study, slower and faster speed control of the virtual hand required participants to actually reach longer and shorter, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…The judgment of agency also involves sensorimotor integration, but its cognitive processes differ from delay detection, and are influenced by several additional factors, including intention and thoughts. For example, intentional effort [20] and goals [21] predictability [22] are reported to influence the explicit SoA. In addition, a previous study [23] reported the different time window of agency disruption compared with the present results, in which healthy participants were asked to judge SoA of their own hand, rather than a square object.…”
Section: Discussionmentioning
confidence: 57%